Uji Cemaran Coliform Menggunakan Uji MPN pada Air Sumur Gali, Sumur Bor dan PDAM - Fatimah, Cut; Safriana, Safriana; Andriani, Sindy (Journal of Pharmaceutical and Health Research, 2024)
Physical, biological, and chemical parameters form the environmental health quality standards for water media used for sanitary hygiene needs. These parameters must be checked periodically by the laws and regulations contained in the Minister of Health Regulation Number 32 of 2017. One of these requirements is the MPN limit, which is a maximum total Coliform count of 50 colonies per 100 milliliters and requires the absence of Escherichia coli. This study was to ascertain whether PDAM water, borehole, and dug well water in the Cinta Rakyat Village area of Percut Sei Tuan Deli Serdang were contaminated by Escherichia coli and the MPN Coliform index. A 3:3:3 tube series consisting of a prediction test using Lactose Broth (LB) media, a confirmation test using Brilliant Green Lactose Broth (BGLB) media, and a complementary test using Eosin media was used to conduct a microbiological contamination test using the Most Probable Number (MPN) Coliform method. Gram stain with methylene blue agar (EMBA). Six water samples from dug wells, six from boreholes, and one PDAM water sample from the homeowner's residence were used for testing. The samples were randomly selected. The findings showed that two well water samples - ASGD 1 with 75 colonies/100 mL and ASGD 6 with 75 colonies/100 mL - exceeded the total Coliform limit. Six samples taken from dug wells were positive for fecal coliform. The colony count for ASGD 1 was 15/100 mL, ASGD 2 was 7/100 mL, ASGD 3 was 7/100 mL, ASGD 4 was 15/100 mL, ASGD 5 was 4/100 mL, and ASGD 6 was 20/100 mL. Two samples from boreholes were positive for fecal coliform. There were 4 colonies/100 mL for ASBD 2 and 7 colonies/100 mL for ASBD 4. PDAM water samples did not contain non-fecal coliforms and fecal coliforms.